Stress fractures in the central metatarsal in female patients - Lopes, Flávio Romeu; Cervone, Gabriel Lopes de Faria; Torres Filho, Lúcio Carlos Azevedo; Lara, Luiz Carlos Ribeiro; Viana, Rafael Pacheco (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the profile and diagnostic methods of only female patients with stress fracture in the central metatarsal. Methods: Retrospective, descriptive study of patients who were treated on an outpatient basis and diagnosed with stress fractures in the second, third or fourth metatarsals from January 2012 to June 2016. The epidemiological profile, the risk factors presented for the development of this pathology and the diagnostic imaging methods were analyzed. Results: There were 30 patients, with a total of 32 fractures. Fifteen cases of fractures were found in the second metatarsal, 13 in the third and 4 in the fourth. The right foot had 11 fractures, and the left foot had 21. The average patient age was 44.3 years of age. Ten patients had normal body mass index (BMI), 13 were overweight and 7 had Grade I obesity. Sixteen patients were sedentary, and 14 regularly exercised. The diagnosis with radiography at first consultation was 8 cases and 2 after the second consultation. In the other 20 cases, the radiography was negative, and magnetic resonance imaging was requested for diagnostic confirmation. Conclusions: Development of metatarsal stress fractures was observed in the majority of patients who were at least 40 years of age, an age group in which estrogen production has begun to decrease in women. Magnetic resonance imaging is the ideal test for early diagnosis of the lesion. Level of Evidence III; Retrospective Comparative Study.